Freeze-thawing impairs the motility, plasma membrane integrity and mitochondria function of boar spermatozoa through generating excessive ROS - Zhang, Bin; Wang, Yan; Wu, Caihong; Qiu, Shulei; Chen, Xiaolan; Cai, Bingyan; Xie, Huimei (BMC veterinary research, 2021)
Cryopreservation is an efficient way to store spermatozoa and is closely associated with the quality of sperm after the freeze-thaw process. During freeze-thaw cycling, excessive reactive oxygen species (ROS) are produced, and the effects of ROS on boar sperm during cryopreservation have not been identified. In this study, we evaluated the quality of boar spermatozoa in different steps of cryopreservation (extension, cooling, and thawing for 30 min and 240 min) with or without boar-sperm antioxidant (N-acetylcysteine (NAC)). The ROS levels, sperm motility, plasma membrane integrity, mitochondrial activity, sperm chromatin structure, ATP content, and sperm apoptosis were assayed. After thawing, the ROS level and sperm apoptosis were significantly increased, and the sperm motility, plasma membrane integrity, mitochondrial activity, sperm chromatin structure, and ATP content were significantly impaired compared with those at the extension period and cooling period. Moreover, the addition of N-acetyl L-cysteine (NAC) reversed these changes. The freeze-thawing of boar spermatozoa impaired their motility, plasma membrane, mitochondrial activity, sperm chromatin structure and apoptosis by producing excessive ROS. Thus, the downregulation of ROS level by antioxidants, especially the NAC, is important for manufacturing frozen pig sperm to increase reproductive cells and livestock propagation, as well as to improve the application of frozen semen in pigs worldwide.